Tumor-associated autoantibodies from mouse breast cancer models are found in serum of breast cancer patients - Sasha E. Stanton (Nature Portfolio, 2021)
Abstract B cell responses to tumor antigens occur early in breast tumors and may identify immunogenic drivers of tumorigenesis. Sixty-two candidate antigens were identified prior to palpable tumor development in TgMMTV-neu and C3(1)Tag transgenic mouse mammary tumor models. Five antigens (VPS35, ARPC2, SERBP1, KRT8, and PDIA6) were selected because their decreased expression decreased survival in human HER2 positive and triple negative cell lines in a siRNA screen. Vaccination with antigen-specific epitopes, conserved between mouse and human, inhibited tumor growth in both transgenic mouse models. Increased IgG autoantibodies to the antigens were elevated in serum from women with ductal carcinoma in situ (DCIS) and invasive breast cancer (IBC). The autoantibodies differentiated women with DCIS from control with AUC 0.93 (95% CI 0.88–0.98, p < 0.0001). The tumor antigens identified early in the development of breast cancer in mouse mammary tumor models were conserved in human disease, and potentially identify early diagnostic markers in human breast tumors.